2020
DOI: 10.1007/978-3-030-34226-5_11
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and Continuous Multi-utility Representations of Nontotal Preorders: Some Considerations Concerning Restrictiveness

Abstract: A continuous multi-utility fully represents a not necessarily total preorder on a topological space by means of a family of continuous increasing functions. While it is very attractive for obvious reasons, and therefore it has been applied in different contexts, such as expected utility for example, it is nevertheless very restrictive.In this paper we first present some general characterizations of the existence of a continuous order-preserving function, and respectively a continuous multi-utility representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Then σ(X, C(X, t, R)) is also useful. Indeed, every total preorder that is continuous with respect to σ(X, C(X, t, R)) is also continuous with respect to t according to Bosi and Zuanon, Theorem 2.23, ( 9) ⇒ (1) of [21]. Then there exists a utility representation u : X → R that is continuous with respect to t, hence u is continuous with respect to σ(X, C(X, t, R)).…”
Section: New Characterization Of Useful Topologiesmentioning
confidence: 99%
“…Then σ(X, C(X, t, R)) is also useful. Indeed, every total preorder that is continuous with respect to σ(X, C(X, t, R)) is also continuous with respect to t according to Bosi and Zuanon, Theorem 2.23, ( 9) ⇒ (1) of [21]. Then there exists a utility representation u : X → R that is continuous with respect to t, hence u is continuous with respect to σ(X, C(X, t, R)).…”
Section: New Characterization Of Useful Topologiesmentioning
confidence: 99%
“…Bosi and Herden [14,Theorem 3.1] showed that a topology is useful if and only if the topology generated by every complete separable system is second countable. In particular, this latter result can be regarded as the simplest axiomatization of useful topologies, even if it, nevertheless, invokes the concept of a complete separable system (see Bosi and Zuanon [16,Definition 2.20]).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we have that E xy is a complete decreasing separable system on (X, t) such that x ∈ E , y ∈ E for every E ∈ E xy . Then the thesis follows from Bosi and Zuanon Remark 2.21, 2 in [19], since to every complete decreasing separable system we can associate a continuous increasing function in a very natural way.…”
mentioning
confidence: 95%